Implementasi Green Accounting Berbasis University Social Responsibility (USR) - Vindi Pronika Sytia Putri; Dwi Suhartini; Astrini Aning Widoretno (BALANCE: Economic, Business, Management and Accounting Journal, 2021)
This study aims to determine whether there are differences in the application of University Social Responsibility based on green accounting at Petra Christian University and Widya Mandala University. This study uses quantitative methods. The population in this study were Petra Christian University and Widya Mandala University. The sampling technique used is purposive sampling. The number of samples collected is as many as 65 respondents. Data collection method using a questionnaire using Google Form. In this study, the hypothesis was tested using an independent sample-T test with SPSS 25 analysis tool. This study showed that the variables of environmental involvement and environmental reporting were statistically different between Petra Christian University and Widya Mandala University. While the other two variables, namely ecological awareness and ecological audit, there is no difference. Keywords                    : Green Accounting; University Social Responsibilities (USR); Universitas Kristen Petra; Universitas Widya MandalaCorrespondence to      : astrini.widoretno.ak@upnjatim.ac.id Penelitian ini bertujuan untuk mengetahui apakah terdapat perbedaan penerapan University Social Responsibility berbasis green accounting pada Universitas Kristen Petra dengan Universitas Widya Mandala. Penelitian ini menggunakan metode kuantitatif. Populasi dalam penelitian ini adalah Universitas Kristen Petra dan Universitas Widya Mandala. Teknik pengambilan sampel yang digunakan adalah purposive sampling. Jumlah sampel yang terkumpul adalah sebanyak 65 responden. Metode pengumpulan data menggunakan kuesioner dengan menggunakan Google Form. Dalam penelitian ini uji hipotesis menggunakan uji independent sample-T test dengan alat analisis SPSS 25. Hasil penelitian ini menunjukan variabel keterlibatan lingkungan dan pelaporan lingkungan yang secara statistik memiliki perbedaan antara Universitas Kristen Petra dan Universitas Widya Mandala. Sementara dua variabel lainnya, yaitu kepedulian lingkungan dan audit lingkungan tidak terdapat perbedaan. Kata Kunci                  : Green Accounting; University Social Responsibilities (USR); Universitas Kristen Petra; Universitas Widya Mandala